A common SLC26A4-linked haplotype underlying non-syndromic hearing loss with enlargement of the vestibular aqueduct. Issue 10 (5th August 2017) - Chattaraj, Parna; Munjal, Tina; Honda, Keiji; Rendtorff, Nanna D; Ratay, Jessica S; Muskett, Julie A; Risso, Davide S; Roux, Isabelle; Gertz, E Michael; Schäffer, Alejandro A; Friedman, Thomas B; Morell, Robert J; et al.
Abstract : Background: Enlargement of the vestibular aqueduct (EVA) is the most common radiological abnormality in children with sensorineural hearing loss. Mutations in coding regions and splice sites of the SLC26A4 gene are often detected in Caucasians with EVA. Approximately one-fourth of patients with EVA have two mutant alleles (M2), one-fourth have one mutant allele (M1) and one-half have no mutant alleles (M0). The M2 genotype is correlated with a more severe phenotype. Methods: We performed genotype–haplotype analysis and massively parallel sequencing of the SLC26A4 region in patients with M1 EVA and their families. Results: We identified a shared novel haplotype, termed CEVA (Caucasian EVA), composed of 12 uncommon variants upstream of SLC26A4 . The presence of the CEVA haplotype on seven of ten 'mutation-negative' chromosomes in a National Institutes of Health M1 EVA discovery cohort and six of six mutation-negative chromosomes in a Danish M1 EVA replication cohort is higher than the observed prevalence of 28 of 1006 Caucasian control chromosomes (p<0.0001 for each EVA cohort). The corresponding heterozygous carrier rate is 28/503 (5.6%). The prevalence of CEVA (11 of 126) is also increased among M0 EVA chromosomes (p=0.0042). Conclusions: The CEVA haplotype causally contributes to most cases of Caucasian M1 EVA and, possibly, some cases of M0 EVA. The CEVA haplotype of SLC26A4 defines the most common allele associated with hereditary hearing loss in Caucasians. The diagnostic yield and prognostic utility of sequence analysis of SLC26A4 exons and splice sites will be markedly increased by addition of testing for the CEVA haplotype.